2016
DOI: 10.1371/journal.pone.0156763
|View full text |Cite
|
Sign up to set email alerts
|

Histones Induce the Procoagulant Phenotype of Endothelial Cells through Tissue Factor Up-Regulation and Thrombomodulin Down-Regulation

Abstract: The high circulating levels of histones found in various thrombotic diseases may compromise the anticoagulant barrier of endothelial cells. We determined how histones affect endothelial procoagulant tissue factor (TF) and anticoagulant thrombomodulin (TM). Surface antigens, soluble forms, and mRNA levels of TF and TM were measured by flow cytometry, ELISA, and real-time RT-PCR, respectively. TF and TM activity were measured using procoagulant activity, thrombin generation, or chromogenic assays. Involvement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 35 publications
5
54
1
1
Order By: Relevance
“…4647 In addition, histones, elastase, and MPO-generated hypochlorous acid each induce endothelial TF production. 48495036 Supporting these in vitro studies, clinical data implicate NETs in coronary disease, venous thrombosis, and other thrombotic conditions. 51525354 Thrombi retrieved from the culprit arteries of ACS patients show higher levels of NET markers.…”
Section: A Special Role For Granulocytes and Neutrophil Extracellularmentioning
confidence: 91%
“…4647 In addition, histones, elastase, and MPO-generated hypochlorous acid each induce endothelial TF production. 48495036 Supporting these in vitro studies, clinical data implicate NETs in coronary disease, venous thrombosis, and other thrombotic conditions. 51525354 Thrombi retrieved from the culprit arteries of ACS patients show higher levels of NET markers.…”
Section: A Special Role For Granulocytes and Neutrophil Extracellularmentioning
confidence: 91%
“…106 Other therapeutic targets that have potential to address histone-dependent NET-mediated cytotoxicity include inter-alpha inhibitor protein, chondroitin sulfate, and high molecular weight hyaluronan for their ability to bind and neutralize histones. 107 Histones may also play a role in thrombosis by upregulating tissue factor and downregulating thrombomodulin, [108][109][110] or by stimulating the release of von Willebrand factor from the endothelium. 111 Together, histones remain a key effector in NET-mediated microvascular hyperpermeability, and more studies to elucidate downstream signaling mechanisms are needed to fully understand their role in disrupting the endothelial barrier.…”
Section: Histonesmentioning
confidence: 99%
“…To date, one of the sole proposed mechanisms implicated in TF expression induced by histones in monocytes is the activation of the TLR2-4/nuclear factor-κB pathway. In that report, it was demonstrated that the selective blockade of TLR2 or TLR4 inhibited the overexpression of TF following activation with H4, among other histones (13). Notably, the expression of TLR4 has been reported in hepatocytes and it may be implicated in the overexpression of hemostatic factors and/or HNF4α as well as TF (39).…”
Section: Discussionmentioning
confidence: 94%
“…The pathogenic role of histones in thrombosis was first proposed by showing that injection of histones in mice induced thrombotic lesions similar to those observed in severe sepsis (12). Indeed, histones have been reported to induce tissue factor (TF; also known as factor III) upregulation and thrombomodulin downregulation leading to a procoagulant phenotype, hence they are considered as damage-associated molecular patterns (DAMPs) (13). DAMPs are recognized as danger signals by Toll-like receptors (TLRs), but the molecular mechanism remains unclear (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%